1998
DOI: 10.1177/07399863980201002
|View full text |Cite
|
Sign up to set email alerts
|

Latino Students and College Entrance Exams: How Much Do They Really Matter?

Abstract: Because many colleges and universities reduce the weight of college entrance exam (e.g., Scholastic Aptitude Test [SAT]) scores for otherwise high-achieving minority students, the common wisdom has been that low SAT scores are relatively benign for Latino students with high grade point averages (GPAs). This study questioned that assumption and asked whether test scores affect other opportunities, such as scholarships; whether the scores erode the confidence of students who score low; and whether low test score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 3 publications
1
10
0
Order By: Relevance
“…African American and Hispanic students are often not well prepared for college admissions tests and often score below their white peers. Many have not taken rigorous courses that would enable them to perform well on these tests and report not preparing for the tests (Gándara & López, 1998). They may not fully realize that these tests are an integral part of the college admissions process and consequently fail to prepare for them.…”
Section: Study Results: College Planning Resources College Admission mentioning
confidence: 99%
“…African American and Hispanic students are often not well prepared for college admissions tests and often score below their white peers. Many have not taken rigorous courses that would enable them to perform well on these tests and report not preparing for the tests (Gándara & López, 1998). They may not fully realize that these tests are an integral part of the college admissions process and consequently fail to prepare for them.…”
Section: Study Results: College Planning Resources College Admission mentioning
confidence: 99%
“…Students are sent the message that their entire educational career depends on which percentile they obtain their score as depending on the percentile students will either obtain access to or get locked out of certain programs and resources (Goldschneider, 2006). Representatives of educational institutions also keep sending the message to prospective students that if they want to obtain admission in their institution, they must score high in the standardized entrance examination (Gandara & Lopez, 1998). Organizations, such as the College Board, also play a double standard because on one hand they tell the institutions that they must not set percentile requirements for examinations such as the SAT when making admission decisions and, on the other hand, they publish documentation listing the “cut off” percentiles of the SAT score for approximately 20 different institutions (Goldschneider, 2006).…”
Section: Aptitude/entrance Exams In the Era Of The Panopticonmentioning
confidence: 99%
“…However, when it comes to the SAT and other forms of entrance examinations, the bilingual students will obtain significantly lower scores than their monolingual peers. On the same note, Gandara and Lopez (1998) studied bilingual students in California and they found that while bilingual students can be good students in every sense of the word, such as obtaining high GPA levels and otherwise exhibit a great deal of potential, when it comes to the SAT and/or the ACT examinations, bilingual students shall perform poorly. In other words, well-performing academically inclined bilingual students will obtain high GPAs and can be labeled as the strong student; however, when it comes to doing a standardized entrance examination or doing a standardized aptitude examination, they shall do poorly.…”
Section: The Bilingual and The Minority Studentmentioning
confidence: 99%
See 1 more Smart Citation
“…Variables such as gender, age at entry, social class, interest in college, willingness to study, time available for study and the quality of that study time have all been identified as factors that impact on, or mediate, to varying degrees, student performance in higher education. Other non-cognitive variables that have been identified include attitudes (House 1994) community service (Ancis & Sedlacek 1997), self-concept (Gardara & Lopez 1998) and self-control (Wolfe & Johnson 1995). In the Irish context, for example, both Lynn (1996) andLynch et al (1999) have shown that there are very real differences in the degree/diploma results of men and women, with men awarded significantly higher grades than women, although internationally the proportion of men and women getting good degrees (that is, a first class or upper second class honours degree) is more or less the same, with men awarded more first and third class degrees than women (see Rudd 1984;Clarke 1988;Chapman 1996b).…”
Section: Introductionmentioning
confidence: 99%